Comparative Study of Concrete with Polypropylene and Polyethylene Terephthalate Waste Plastic as Partial Replacement of Coarse Aggregate - Md. Jahidul Islam (Advances in Civil Engineering)
Production of plastic has risen significantly in the last 60 years worldwide, and around 10% of this plastic is turned into solid waste. This plastic becomes an environmental hazard in the absence of appropriate recovery methods. Incorporating waste plastic in concrete is an alternate way to recycle this waste plastic. Polypropylene (PP) and polyethylene terephthalate (PET) are two of the most widely used plastic scarcely recovered and recycled. Therefore, in the present study, both PP and PET are used as a partial replacement (10%, 20%, and 30% by volume) of coarse aggregate. These concretes are compared for three different water-cement ratios (0.42, 0.48, and 0.57). Properties such as workability, density, compressive, and tensile strengths are compared. Concrete with PP aggregate has shown as much as 39% higher compressive strength and 9% lower density than brick aggregate concrete. On the other hand, concrete with PET aggregate has displayed as much as 53% reduction in compressive strength compared to the reference concrete. Furthermore, it demonstrates higher workability and lower density. Equations are proposed to describe relationships between compressive and splitting tensile strengths of concrete, including the effect of plastic aggregate percentages. Cost analysis of the concrete reveals that incorporating waste plastic in concrete is more expensive than the regular brick aggregate concrete. Still, up to 10%, PP can be used in concrete, considering the gain in compressive strength.